Effect of dietary fat and food consistency on gastroparesis symptoms in patients with gastroparesis. Issue 4 (19th January 2015) - Homko, C. J.; Duffy, F.; Friedenberg, F. K.; Boden, G.; Parkman, H. P.
Abstract: Background: Nutrition therapy for gastroparesis focuses on reducing meal size, fiber, fat intake, and increasing liquids intake relative to solid foods. Evidence to support these dietary interventions has been anecdotal. The aim of this study was to determine the effect of fat intake and solid/liquid meal consistency on symptoms in gastroparesis. Methods: Twelve patients with gastroparesis were studied on four separate days receiving one of four meals each day in a randomized order: high‐fat solid, high‐fat liquid, low‐fat liquid, and low‐fat solid meal. At each visit, eight gastrointestinal symptoms were rated from 0 (none) to 4 (very severe) every 15 min, before and for 4 h after meal ingestion. Key Results: There was an increase in the total symptom score in the following order: high‐fat solid > low‐fat solid > high‐fat liquid > low‐fat liquid. For the high‐fat solid meal, symptoms remained elevated throughout the 4 h postprandial period. Severity of nausea more than doubled after the high‐fat solid meal, whereas the low‐fat liquid meal caused the least increase in nausea. Conclusions & Inferences: A high‐fat solid meal significantly increased overall symptoms among individuals with gastroparesis, whereas a low‐fat liquid meal had the least effect. With respect to nausea, low‐fat meals were better tolerated than high‐fat meals, and liquid meals were better tolerated than solid meals. These data provide support for recommendations that low‐fat and increased liquid content meals are best tolerated in patients with symptomatic gastroparesis. Abstract : The aim of this study was to determine the effect of fat intake and solid/liquid meal consistency on symptoms in gastroparesis. This figure shows that a high‐fat solid meal increased overall symptoms among individuals with gastroparesis, whereas a low‐fat liquid meal had the least effect. These data provide support for recommendations that low‐fat and increased liquid content meals are best tolerated in patients with symptomatic gastroparesis.